PEMBANGUNAN KOSWER PEMBELAJARAN BERBANTUKAN KOMPUTER BAGI TOPIK PROSES PENERBITAN ANIMASI - Hamzah, Norhasyimah; Ariffin, Arihasnida; Rubbani, Siti Nurkamariah; Subramanian, Tamil Selvan (Online Journal for TVET Practitioners, 2018)
Animation Technology is one of the courses for the Bachelor of Vocational Education (Creative Multimedia) degree program at the Faculty of Technical and Vocational Education (FPTV), Universiti Tun Hussein Onn Malaysia (UTHM). This study aims to design, develop and evaluate a courseware for the topic of animation publishing. Additionally, this study examines the usability of courseware for the topic of animation publishing process to the three experts in Creative Multimedia field. The development methodology is based on ASSURE model which has six phases namely analyse learner phase, state objective phase, select method, media and materials phase, utilize media and materials phase, require learner participation phase evaluate and revise phase. Therefore, in the evaluation phase and review, the developer assesses three experts in the Creative Multimedia field and lecturers who teaches the Animation Technology subject. There are three designs that are evaluate by three experts such as for information design, interaction design and interface design. Experts are Creative Multimedia lecturers with 10 to 15 years of experience in design and subject Animation Technology. The findings of this study showed that the three designs met the assessment where improvements made after the experts expressing improvements to education courseware developed. In conclusion, the development of courseware is expect to help students for better understand about the topic.